Debating collaboration and complicity in war crimes trials in Asia, 1945-1956 - Lingen, Kerstin von (Springer International Publishing, 2017)
Debating Collaboration and Complicity in War Crimes Trials in Asia, 1945-1956 -- Contents -- List of Contributors -- List of Tables -- War Crimes Trials in Asia: Collaboration and Complicity in the Aftermath of War -- Collaboration and Complicity as a Legal Problem -- Decolonization as the Background of Trials on Collaboration -- The Dimension of Time -- Conclusion -- Notes -- Koreans in the Trials of Japanese War Crimes Suspects -- Notes -- Defining Colonial "War Crimes": Korean Debates on Collaboration, War Reparations, and the International Military Tribunal for the Far East -- Notes -- Oaths of Allegiance in the Singapore Trials -- Introduction -- Legal Framework and Socio-Political Context of Singapore Trials -- The Impossible-to-Renounce Approach: The Trials of Ikegami Tomoyuki and Others and Takashima Shotaro and Another -- Ikegami Tomoyuki and Others -- Takashima Shotaro and Another -- Criminal Law Approach: DJAG Review Reports of Ikegami Tomoyuki and Others and Takashima Shotaro and Another -- Conclusion -- Notes -- Puppets, Profiteers and Traitors: Defining Wartime Collaboration in the Dutch East Indies, 1945-1949 -- Collaboration in a Colonial Setting -- Ideas and Expectations -- Jurisdiction -- Puppets, Profiteers and Traitors -- Amnesty Decree -- Conclusion -- Notes -- Between Postoccupation and Postcolonial: Framing the Recent Past in the Philippine Treason Amnesty Debate, 1948 -- Failed Trials and Amnesty in the Philippine Treason Trials -- "Different Conceptions of Serving One's Country" - Quintin Paredes and Charles de Gaulle -- "That Which is Reasonably Required by Civilized Justice" -- "The Glorious Pages of Our Past" -- Notes -- Japanese Medical Atrocities and the Collaboration of the Scientific Elites: Postwar Perspectives -- Notes
Gesehen am 23.01.2019
Keywords: Geschichte 1945-1956; Strafverfahren; Kollaboration; Kriegsverbrechen; Zweiter Weltkrieg; Asien